Modal Intelektual, Manajemen Pengetahuan dan Kinerja UMKM serta Kecepatan dan Kualitas Inovasi sebagai Variabel Mediasi - Cahyaningati, Retno; Muttaqien, Fauzan; Sulistyan, Riza Bahtiar; Paramita, Ratna Wijayanti Daniar; Ana, Selvia Roos (E-Jurnal Akuntansi, 2022)
The study explores the relationship between intellectual capital, knowledge management on firm performance and the role of speed and quality of innovation as mediating variables. Data was collected from MSME actors through a structured questionnaire. The sample used as many as 275 MSME actors in Lumajang Regency and analyzed using Smart PLS 3. The results of the study prove that intellectual capital and knowledge management significantly affect innovation, both the speed of innovation and the quality of innovation. Intellectual capital cannot directly affect the company's performance, but knowledge management can directly affect the company's performance. Overall, the role of speed and quality of innovation mediates the relationship between intellectual capital and knowledge management on firm performance. Keywords: Intellectual Capital; Knowledge Management; Innovation; MSME Performance.